The Role of Human Papillomavirus in Bowenoid Papulosis - Yuli Wahyu Rahmawati; Dwi Murtiastutik; Sjahjenny Mustokoweni (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Human Papillomavirus (HPV) infection can be associated with a variety of cutaneous as well as mucosal manifestations. Some types of HPV are associated with increased risk of epithelial malignancies; these have been divided into low-risk and high-risk types based on their oncogenic potential. Bowenoid papulosis (BP) strongly associated with high risk type. Purpose: To provide information to health workers, in order to be more concern about BP.Review: The term BP refers to multifocal papular lesions on the genitalia with histological features similar to squamous cell carcinoma (SCC) in situ or Bowen’s Disease (BD). Its clinical manifestation is characterized by multiple brownish or erythematous papules located in the anogenital region, affecting mostly young adults with an active sex life. Clinically, it must be differentiated from seborrheic keratosis, and melanocytic nevus. Bowenoid papulosis is strongly associated with HPV 16.Conclusion: The natural course of BP is unpredictable, the lesions may increase, decrease, and even disappear spontaneously. Progression to an invasive SCC has been estimated in 2.6% of cases, HPV type 16 is the most frequent causative agent of BP.